Increased fibrinogen levels at diagnosis are associated with adverse outcome in patients with acute myeloid leukemia. Issue 4 (15th June 2016) - Berger, Martin D.; Heini, Alexander D.; Seipel, Katja; Mueller, Beatrice; Angelillo‐Scherrer, Anne; Pabst, Thomas
Abstract: Increased plasma fibrinogen levels are associated with shortened overall survival (OS) in some solid tumor types. In contrast, the prognostic significance of varying fibrinogen levels in acute myeloid leukemia (AML) at diagnosis is unknown. In this study, we assessed the prognostic significance of fibrinogen levels in AML patients. In a comprehensive retrospective single‐center study, we determined the survival rates of 375 consecutive AML patients undergoing at least one cycle of intensive chemotherapy induction treatment. Patients were dichotomized between low (<4.1 g/L) and high fibrinogen levels (≥4.1 g/L) at diagnosis of AML before initiation of treatment. Subsequently, quartile ranges were applied to analyze the association of varying fibrinogen levels on survival. We observed that the rates of complete remission, early death, and admission to intensive care unit were equal in the low versus high fibrinogen group. However, OS was significantly better in the low fibrinogen group (27.3 vs 13.5 months; p  = 0.0009) as well as progression‐free survival (12.3 vs 7.8 months; p  = 0.0076). This survival difference remained significant in the multivariate analysis ( p  = 0.003). Assessing quartiles of fibrinogen values, we further confirmed this observation. Our data suggest that high fibrinogen levels at diagnosis of AML are associated with unfavorable OS and progression‐free survival but not with increased mortality during induction treatment. Copyright © 2016 John Wiley & Sons, Ltd.